A first assessment of genetic variability in the Eurasian Stone‐curlew Burhinus oedicnemus. (23rd May 2014) - Mori, Alessia; Baldaccini, Natale E.; Baratti, Mariella; Caccamo, Chiara; Dessì‐Fulgheri, Francesco; Grasso, Rosario; Nouira, Said; Ouni, Ridha; Pollonara, Enrica; Rodriguez‐Godoy, Felipe; Spena, Maria T.; Giunchi, Dimitri; et al.
<x xml:space="preserve">Abstract</x> The Eurasian Stone‐curlew is a species of conservation concern in Europe. We investigate for the first time the extent of population structure among populations sampled from six geographical areas, representing four subspecies inhabiting the western part of the species' distribution. Neither mitochondrial nor nuclear markers fully supported current subspecies boundaries. However, both markers support significant differentiation of the Canary Island populations from those sampled from the Mediterranean. Further work is needed to establish the taxonomic status of this potentially distinct Macaronesian taxon. More broadly, further genetic research is required to design and implement an effective conservation plan for this species.